Linguistics Metafunctions of Academically Historical Engineering Text and Its Implications towards in Teaching Reading in ESP Context - Rita Darmayanti (ELITE JOURNAL, 2020)
This paper aims at exploring the linguistics characteristics of historical text in academically engineering textbook by investigating the linguistics metafunctions of the text based on Systemic Functional Linguistics theory. Investigating the textualization of historical text to achieve its roles and purposes for presenting and recounting events in the past requires critical analysis on the use of lexico-grammatical and discourse-semantic linguistics resources by identifying the textual, interpersonal, and ideational functions of the text. The findings showed that historical text, as kind of text that belongs to the genre of recount, is structured by (1) the constant and continuous thematic progression to point out the remarkable events happened in the past, (2) declarative clauses having positive polarity and validity for the past time, (3) the predominance of material clauses showing the emphasizing on recounting the action done by engineers in the past. This study suggests teacher to provide explicit assistance for students to understand the meaning and function of the elements constructing the nominal group which textualize the lexical density of the text and the clause complexes in terms of clauses’ dependency relation based on their meaning, context and function.